Hexanitrato complexes and hybrid double perovskites of Am3+ and Cm3+. Issue 85 (11th October 2022) - Tarlton, Michael L.; Skanthakumar, Suntharalingam; Vallet, Valérie; Wilson, Richard E.
Abstract : Isostructural, homoleptic twelve-coordinate nitrato complexes of the 5f-ions Am and Cm are reported that occur as hybrid double perovskites. Abstract : The synthesis and structures of the homoleptic hexanitrato complexes of Am(iii ) and Cm(iii ), [(CH3 )4 N]2 KAn(NO3 )6 are reported. These compounds form a double perovskite structure type, A2 B′BX6, crystallizing in the cubic space group Fm 3̄ m . Their electronic properties, as calculated using the Quantum Theory of Atoms in Molecules, are reported and compared to their lanthanide homologues Eu(iii ) and Gd(iii ).